Prevalence of Staphylococcus aureus and methicillin resistant Staphylococcus aureus (MRSA) in the oral cavity. Issue 9 (September 2015) - Koukos, Georgios; Sakellari, Dimitra; Arsenakis, Minas; Tsalikis, Lazaros; Slini, Theodora; Konstantinidis, Antonios
Highlights Prevalence of S. aureus and MRSA was examined by PCR in the oral cavity. S. aureus was detected in 18% of all participants (healthy, gingivitis, periodontitis). S. aureus should be considered a member of the transient flora. The oral cavity is an unusual habitat of MRSA.